Transformational Leadership in Education: Improving Work Ethic and Professional Commitment of Teachers - Supendi, Pepen; Gaffar, M. Andriana; Rosa, Ade Tutty R.; Fahrurozi, Fahrurozi (Lectura : Jurnal Pendidikan, 2025)
Effective school leadership shapes teachers’ work ethics and overall performance. In the context of MTs Darul Hikam Bandung, understanding how principal leadership influences teacher motivation and commitment is essential. Although transformational leadership has been recognized for fostering a positive school climate, challenges such as declining teacher engagement and productivity persist. This study explores the principal’s leadership strategies for improving teachers’ work ethics and enhancing their commitment to teaching. It examines the impact of transformational leadership on teacher motivation and job satisfaction. A qualitative research approach was employed, utilizing in-depth interviews with principals, teachers, administrative staff, and classroom observations. Thematic analysis was applied to identify leadership practices and their effects on teacher motivation and professional commitment. The findings revealed that the principal adopted a transformational leadership style, emphasizing role modelling, effective communication, and continuous professional development. Teachers reported increased motivation and a greater sense of value due to the principal’s support and responsiveness. Key strategies included regular training sessions, collaborative decision-making, and fostering a supportive work environment to help teachers overcome instructional challenges. The results demonstrated that transformational leadership positively influenced teachers’ commitment and job satisfaction. Transformational leadership significantly enhances teachers’ work ethics by fostering interpersonal relationships, promoting professional development, and ensuring clear communication. This study provides valuable insights for educational stakeholders to strengthen teacher engagement and improve school effectiveness. Further research is recommended to validate these findings in diverse educational settings.